The Low Friction Coefficient and High Wear Resistance UHMWPE: The Effect of Pores on Properties of Artificial Joint Materials - Chunmin Yang; Junhua Zhang; Honglin Yue; Xueqin Kang (Lubricants)
Ultrahigh-molecular-weight-polyethylene (UHMWPE) is extensively applied to make bone and cartilage implants in the field of biomaterial application. UHMWPE matched with a metal or ceramic component withstands the long-term effect of cyclic stress, which induces UHMWPE serious wear, and affects the service life of the artificial joint. This investigation focuses on the influence of pores on the mechanical and tribological property of UHMWPE. The porosity, crystallinity, yield strength, tensile strength, hardness, compression yield strength, creep resistance, wettability, friction performance, and wear mechanism of solid and porous UHMWPE were evaluated and compared. The research results indicated that the pore had a remarkable influence on the mechanical, friction, and wear property of UHMWPE. The porosity of porous UHMWPE was 29.7% when 50 wt. % sodium chloride (NaCl) was added and the pore size was about 200 μm. The crystallinity, hardness, creep resistance, strength, and elongation decreased after NaCl was added and dissolved. However, the yield strength in the tensile and compression test was closer to that of the natural cartilage. The friction coefficient and wear loss of porous UHMWPE were higher than that of solid UHMWPE in dry conditions, but these values of porous UHMWPE were lower than that of solid UHMWPE in the calf serum lubrication condition. The main wear mechanism of porous and solid UHMWPE was abrasive. The lubricity of calf serum reduced wear surface scratches and furrows, especially for porous UHMWPE.